Enhancing brand coolness through perceived luxury values: insight from luxury fashion brands - Loureiro, S. M. C.; Jiménez-Barreto, J.; Romero, J. (Journal of Retailing and Consumer Services, 2020)
Consumers of luxury brands have been described as seekers of products that can offer a signaling value to present to others but also a value for their self-concepts in an existentialist spirit potentially linked to being “cool or not.” Prior studies have conceptualized brand coolness and evaluated its impact on consumer responses to brands. However, few studies have contextualized the construct of brand coolness concerning luxury brand realism. We assessed the semiotic tension that luxury brand consumers feel between self-concept and self-presentation to others via a theoretical consideration of four antecedents of brand coolness: individual, social, financial, and functional luxury values; and one intentional outcome such as consumers' passionate desire to use luxury fashion brands. Our findings indicated that luxury values positively influence brand coolness, and brand coolness positively influences passionate desire. We further confirmed that brand coolness plays a complementary mediating role between luxury values and passionate desire. A final contribution is to invite brand managers to consider how luxury values and brand coolness might be used proactively to drive consumers' passionate desires in the relationships with luxury fashion brands.